147k views
2 votes
Answers fast please. 1.) y=x−63x+2y=8 Use the substitution method. A.) (4, −2) B.) (14, 8) C.) (0, −6) D.) (3, −3) 2.) What is the x-coordinate of the solution for the system of equations? {y−x=910+2x=−2y X= what? 3.) What is the y-coordinate of the solution for the system of equations? {y=3x−1x−y=−9 Y=what?

User Bendecoste
by
5.5k points

2 Answers

2 votes
1.
A.) (4, −2)

2.
x = -7
y = 2

3.
x = 5
y = 14
User Antoniom
by
5.6k points
3 votes

QUESTION 1

The given system of equation is


y=x-6...eqn1

and



3x+2y=8...eqn2


Let us substitute equation (1) into equation (2) to get,


3x+2(x-6)=8


We expand the bracket to get,


3x+2x-12=8


We simplify to get.


5x-12=8


We group like terms to get


5x=8+12


\Rightarrow 5x=20


\Rightarrow x=4


We now substitute
x=4 in to equation (1) to obtain,



y=4-6=-2


The correct answer is option A.


QUESTION 2

The given system of equations is


y-x=9...eqn1


and


10+2x=-2y...eqn2

We make y the subject in equation (2) to get,


y=-x-5..eqn3


We put equation (3) into equation (1) to obtain,



-x-5-x=9


We group like terms to get,


-x-x=9+5


This implies that,


-2x=14


We divide through by
-2 to get,


x=-7


Hence the x-coordinate is
-7



QUESTION 3

The given system is


y=3x-1..eqn1


and



x-y=-9...eqn2

We make
x the subject in equation (2) to get,


x=y-9...eqn3


We put equation (3) into equation (1) to obtain,



y=3(y-9)-1


We expand the bracket to get,



y=3y-27-1


Group like terms to get,



y-3y=-27-1


We simplify to get;


-2y=-28


This implies that,


y=14


Therefore the y-coordinate is 14.

User Noamk
by
5.5k points